Variable-rate mechanical pruning: a new way to prune vines - Botelho, M. (2021)
Hand pruning is a precise operation, with a visual evaluation of each grapevine to adapt bud load to the vigor. With the advent of mechanical pruning the individual evaluation is lost, and the plant balance relies solely on self-regulation mechanisms. However, precision agriculture provides remote sensing tools for vigor evaluation that allow adapting mechanical pruning to the vine vigor. Variable-rate mechanical pruning (VRMP) could be a way of bringing the best of two worlds: time-efficiency of a mechanized operation and the plant-level accuracy of a hand-made operation. In the present study two different options were investigated as the basis for the bud load prescription map: a) images acquired from the SENTINEL-2 satellite with a spatial resolution of 10 m at processing cost; b) images acquired with a hyperspectral camera from a drone with a spatial resolution of 5 cm at acquisition and processing cost. While the images from SENTINEL-2 allow the individualizing vigor areas, the images from the drone allow evaluating a vegetation index (e.g., NDVI) per single plant. Three different vigor classes were set and, for each, a different cutting distance from the cordon was defined. Two different variable-rate mechanical pruning treatments were established, one with the cutting distance varying between NDVI areas and the other varying between individual plants, both compared with a standard mechanical pruning with a uniform cutting distance. Canopy structure, canopy microclimate, yield and grape composition were assessed to evaluate the performance of each treatment